CURRENT STATUS OF SHORT-TERM MEDICAL TRAINING FOR PHYSICIANS AT TIEN GIANG GENERAL HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of short-term training for physicians and associated factors at Tien Giang General Hospital in 2025.Methods: A cross-sectional descriptive study with analytical components was conducted among 315 physicians at Tien Giang General Hospital in 2025. Data were collected using a self-administered questionnaire and analyzed using Stata 18.Results: The overall satisfaction rate with short-term training was 84.1% (mean score: 4.2 ± 0.45). The highest-rated domains were training schedule notification and teaching staff (89.0%), while training duration and timing were rated lower (79.0%). Satisfaction was higher among physicians with ≥ 3 years of work experience (p = 0.008) and those with postgraduate qualifications (p < 0.001). Training content relevance (OR = 4.11) and increased confidence after training (OR = 11.03; p < 0.001) were significantly associated with satisfaction.Conclusion: Physicians’ satisfaction with short-term training was high; however, improvements in training duration are needed. Content relevance and post-training confidence are key factors influencing satisfaction.
Keywords: short-term training, continuing medical education, physicians, Tien Giang General Hospital.